(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
The importance of this research on Professional Practice in Touristic Administration Degrees and Gastronomy of the Faculty of Administration of the Benemerita Universidad Autonoma de Puebla (BUAP), lies in the purpose of the information collected was provided by undergraduate students, in the development of their Professional Practices (PP) and to determine the degree of learning of the students in their training and accompaniment of the tutor teacher, contributing to interdisciplinary self-knowledge and development of their work skills in the service companies where they perform PP. The measuring instrument was designed and evaluated 120 students of both Bachelor’s degrees in their PP in three time periods - quarters - that are; summer and autumn 2016 and spring 2017, surveying 3 sections: Functions, Work Environment and Administration with 5 questions each of the instrument. Based on the scientific method, two types of variables were considered; the independent variable corresponds to the relationship between the PP of the students. The dependent variable related to improving school use, measurable by an interview aimed at tutor-teachers. The results show relevant points of coincidence that help to enhance the management of their own knowledge in the field of work.